"What we talk about is creating a probability": Exploring the interaction between the anticipation and decision-making processes of professional bowlers and batters in Twenty20 cricket - Marshall, T.; Runswick, O. R.; Broadbent, D. P. (Psychology of Sport and Exercise, 2024)
Expert performers in time constrained sports use a range of information sources to facilitate anticipatory and decision-making processes. However, research has often focused on responders such as batters, goalkeepers, defenders, and returners of serve, and failed to capture the complex interaction between opponents, where responders can also manipulate probabilities in their favour. This investigation aimed to explore the interaction between top order batters and fast or medium paced bowlers in cricket and the information they use to inform their anticipatory and decision-making skills in Twenty20 competition. Eleven professional cricketers were interviewed (8 batters and 3 bowlers) using semi-structured questions and scenarios from Twenty20 matches. An inductive and deductive thematic analysis was conducted using the overarching themes of Situation Awareness (SA) and Option Awareness (OA). Within SA, the sub-themes identified related to information sources used by bowlers and batters (i.e., stable contextual information, dynamic contextual information, kinematic information). Within OA, the sub-themes identified highlighted how cricketers use these information sources to understand the options available and the likelihood of success associated with each option (e.g., risk and reward, personal strengths). A sub-theme of `responder manipulation` was also identified within OA to provide insight into how batters and bowlers interact in a cat-and-mouse like manner to generate options that manipulate one another throughout the competition. A schematic has been developed based on the study findings to illustrate the complex interaction between the anticipation and decision-making processes of professional top order batters and fast or medium paced bowlers in Twenty20 cricket.